The Septuagint from Alexandria to Constantinople: canon, New Testament, church fathers, catenae - Dorival, Gilles (Oxford University Press USA - OSO, 2021)
An authoritative study of the reception of the Septuagint in Alexandria and in the Christian tradition, based on Gilles Dorival's Grinfield Lectures.